2013
DOI: 10.1093/cercor/bhs395
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-DCC Signaling Regulates Corpus Callosum Formation Through Attraction of Pioneering Axons and by Modulating Slit2-Mediated Repulsion

Abstract: The left and right sides of the nervous system communicate via commissural axons that cross the midline during development using evolutionarily conserved molecules. These guidance cues have been particularly well studied in the mammalian spinal cord, but it remains unclear whether these guidance mechanisms for commissural axons are similar in the developing forebrain, in particular for the corpus callosum, the largest and most important commissure for cortical function. Here, we show that Netrin1 initially att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 55 publications
5
114
1
Order By: Relevance
“…In retinotectal axon branching, DCC mediates the netrin-1-induced branch-promoting signal (55). Similarly, growth of TC and callosal axons at the embryonic stages is promoted by netrin-DCC signaling (56)(57)(58)(59). However, the present data show that DCC is not strongly expressed in the thalamus at P14, and its binding to NTN4 is substantially weaker than that of Unc5B (Fig.…”
Section: Discussioncontrasting
confidence: 48%
“…In retinotectal axon branching, DCC mediates the netrin-1-induced branch-promoting signal (55). Similarly, growth of TC and callosal axons at the embryonic stages is promoted by netrin-DCC signaling (56)(57)(58)(59). However, the present data show that DCC is not strongly expressed in the thalamus at P14, and its binding to NTN4 is substantially weaker than that of Unc5B (Fig.…”
Section: Discussioncontrasting
confidence: 48%
“…Whether NRP2 functions as a compensatory factor in Emx1 −/− /C57Bl/6 mice is of interest for future study. In addition, we recently demonstrated that cingulate callosal axons also express the axon guidance receptor DCC, and that these axons are attracted towards its ligand, NTN1, at the midline (Fothergill et al, 2014). Similarly, other short-and longrange axon guidance molecules have been demonstrated to function in regulating neocortical callosal pathfinding (Shu and Richards, 2001;Shu et al, 2003;Andrews et al, 2006;Islam et al, 2009;Nishikimi et al, 2011).…”
Section: Emx1 Mediates Cingulate Callosal Axon Guidance By Regulatingmentioning
confidence: 95%
“…Loss of commissural inhibitory axonal connections of the corpus callosum might produce inappropriate bilateral activation of the sensorimotor cortex (Galléa et al, 2011;Lepage et al, 2012;Fothergill et al, 2013). Alternatively, inappropriate ipsilateral targeting of a subset of corticospinal tract axons could cause the behavioral deficits (Peng and Charron, 2013), consistent with unilateral motor cortex stimulation in DCC pa-tients producing bilateral motor activation (Cincotta et al, 2003;Depienne et al, 2011).…”
Section: Introductionmentioning
confidence: 98%